Estudo de aplicação da pirólise rápida em leito de jorro para valorização de resíduos agroindustriais - Borél, Lidja Dahiane Menezes Santos (2018)
The use of agroindustrial waste as a biomass source for thermo-conversion processes is a promising strategy that combines efficient management and added value generation through the energy densification of these materials. In this sense, studies that correlate the operational conditions of the pyrolysis with the quantity and quality of the products obtained can contribute to the process efficiency. Therefore, the main objective of this work was to study the bio-oil production from biomass by fast pyrolysis in a spouted bed reactor. The pyrolysis application was evaluated for two residues that are abundant in Brazil, coconut residue and brewer’s spent grain (BSG), based on physicochemical properties, the thermal degradation behavior and the products generated. Thermogravimetric analyses were carried out in an inert nitrogen atmosphere (50 mL/min) in the temperature range of 30 to 900ºC at heating rates of 5, 10, 20, 30, 40 and 50°C/min. The kinetic parameters were estimated by isoconversional methods and by independent parallel reactions model (IPR). The composition of the pyrolytic vapors was investigated via Py-GC/MS at 350, 450, 550, 650 and 750°C in an inert helium atmosphere. Both residues had good thermal properties and provided pyrolithic vapors rich in valuable chemicals from an industrial perspective. However, BSG presented more suitable physical properties to handle the sand/biomass mixture in the spout bed, higher volatiles content, better predictive deposition indexes, higher reactivity and more hydrocarbons as pyrolytic products. Conventional pyrolysis of the fixed bed malt produced high HHV (27.1 to 28.3 kJ/g), low ash (11.5%) and sulfur (<0.6%). In the liquid fraction, the presence of phenols and ketones precursors of several compounds in the chemical industry, besides pyrazines, which are used in the pharmaceutical industry. In this way, the valorization potential of BSG by thermochemical conversion was proved. In sequence, the fluid dynamic behavior of mixture of sand and BSG in the spouted bed was evaluated. The tests were performed with mixtures with different mass fraction of BSG (6% to 80%) and static bed height (6.6 cm to 13.4 cm). Empirical equations for predicting the minimum spouting condition and the mixing index were obtained by regression technique. The segregation profile was accentuated by the increase of the bed mass, but it remained acceptable (IM ≈ 1) even for rich biomass mixtures. However, in order to optimize heat transfer from the sand to the biomass, the operating conditions chosen for pyrolysis tests under nitrogen flow (4 m3/h) at 550ºC were the lowest values of the variables xD and Ho. The operation of the experimental unit provided acceptable yields of gas (52.3%), bio oil (42.4%) and char (5.4%) with adequate residence time (from 0.7 to 0.8 s) compared to other operating pyrolysis plants reported in the literature. The bio-oil produced was a mixture that was rich in phenolic compounds; various nitrogenated compounds, precursors of the pharmaceutical industry; and long-chain hydrocarbons.